Polyploidy in Bryum collected from the Syowa Station area, Antarctica - Hiroshi Kanda; Hiroshi Okada (National Institute of Polar Research, 1990)
Bryum pseudotriquetrum (HEDW.) GAERTN., MEYER et SCHERB. and B. amblyodon C. MUELL. collected from the Syowa Station area, Antarctica are karyologically studied with particular regard to the polyploidy. Almost all samples of these two species showed to have n=20. This may be the diploid level derived from x=10. In the present study, however, the triploid level (n=30) was confirmed in one sample of B. pseudotriquetrum, and the morphological features of chromosomes, leaves and cells are compared with those of n=20. Such polyploidy was hitherto unknown in this species. It is possible to say that the polyploidy increases in incidence with latitude in the polar areas.